Collective Sentence Repetition in Developing Arabic Speaking Skills: From Passive Audiences to Active Speakers - Naima Helwa; Khoirul Jamil (Al-Wazan: Journal of Arabic Education, 2026)
Weekly Arabic language activities in non-boarding madrasahs often remain one-way performances in which only a few students speak while most students act as passive listeners. Limited repetition and inconsistent explanation of sentence meanings further restrict students’ participation and development of mahārah kalām. This study aims to analyze how collective sentence repetition encourages passive students to participate in Arabic-speaking activities. A qualitative case study was conducted involving 18 eighth-grade students, consisting of nine active and nine passive students, as well as an Arabic language teacher. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings show that the weekly activity was managed through contextual vocabulary selection, collective sentence repetition, and corrective feedback that avoided embarrassing students. Eight of the nine passive students reported feeling more comfortable and confident when speaking collectively because the fear of making mistakes and being individually judged was reduced. Institutional support strengthened the program, whereas limited frequency, weather dependence, and inconsistent meaning explanation constrained its implementation. This study contributes an inclusive model of bi’ah lughawiyyah by positioning collective sentence repetition as a practical strategy for transforming passive listeners into active Arabic speakers.